Perbedaan Perilaku Pasien Diabetes Mellitus Pria dan Wanita dalam Mematuhi Pelaksanaan Diet - Darusman Darusman (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Diabetes melitus is one of the degenerative disease, which is the amount will increase in the future and needs serious treatment because of complications cause it. Diet is the main therapy to improve and maintain the blood sugar in normal rate. For helping the diabetic patient doing the new diet therapy in their daily living is depend on their attitude and behavior. The long lasting obedience in preparing the meals is one of the most challenge in diet therapy.Method: The aim of this research is for identificated the differences of behavior and the obedience between male and female who have diabetes melitus in diet therapy with descriptive comparative and independent t-test with SPSS version 12.0,Result: The result of this research shows 55,0% males and 70,0% females have bad behavior of the obedience in diet therapy. Beside that 80,0% males and 70,0% females are obey to follow diet therapyConclusion: From the result of this research shows P = 0,093, because P > 0,05, the conclusions is there is no differences of behavior in obedience diet therapy between male and female.Keywords: behavior, obedience, diet, diabetes melitus